Pengembangan Bahan Ajar Ekonomi Berbasis Komik Terhadap Teori Permintaan dan Penawaran - baiq yuliana rizkiwati; Huzain Jailani (Educatio, 2018)
Research and development objectives are: 1) to produce teaching materials based economy comic who will survive and be used for the subsequent years 2) determine the feasibility of teaching materials based economy comic developed by an expert assessment of visual design, subject matter experts, and expert teaching materials, 3) determine the response validator experts and students to the teaching material based economy comics that have been developed, and 4) determine the effectiveness of teaching materials developed comic-based economy. This type of research is the development of research with Borg and Gall models that have been modified into an eight-step development. Data were collected by questionnaires and tests. The results showed that the comic book-based teaching materials economy is very appropriate to use, as evidenced by a score of votes matter experts 81.81% (decent), design expert at 81.33% (decent), and field trials of 79.57% (feasible). Products developed tested on 25 students. The analysis is Paired Sample T-Test through SPSS 19, which showed sig. (2-tail) of 0.00 (less than 0.05) that there are significant differences between the pretest and posttest.